Dissection of a pit – case study - Troy, A.J. (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
Given that ‘Mother Nature’ is the ultimate arbiter in terms of actual material strengths and appropriate pit design, a progressive slope failure experienced at Mine A has highlighted opportunities to improve geotechnical awareness and balanced risk reduction. The dissection of a pit approach uses the unwelcome failure to examine five contributing geotechnical factors, their associated challenges and overall assumptions previously made. The resulting back analysis and focussed material strength re-interpretation highlights the need for regular and ongoing performance reconciliation to identify and resolve inconsistencies within the geotechnical model. With this in mind, it is hoped that elements from the findings will be considered during successive ground investigations, for deposits in related environments.